The microalga Parachlorella kessleri––A novel highly efficient lipid producer. Issue 1 (18th July 2012) - Li, Xiuling; Přibyl, Pavel; Bišová, Kateřina; Kawano, Shigeyuki; Cepák, Vladislav; Zachleder, Vilém; Čížková, Mária; Brányiková, Irena; Vítová, Milada
Abstract The alga Parachlorella kessleri, strain CCALA 255, grown under optimal conditions, is characterized by storage of energy in the form of starch rather than lipids. If grown in the complete medium, the cultures grew rapidly, producing large amounts of biomass in a relatively short time. The cells, however, contained negligible lipid reserves (1–10% of DW). Treatments inducing hyperproduction of storage lipids in P. kessleri biomass were described. The cultures were grown in the absence or fivefold decreased concentration of either nitrogen or phosphorus or sulfur. Limitation by all elements using fivefold or 10‐fold diluted mineral medium was also tested. Limitation with any macroelement (nitrogen, sulfur, or phosphorus) led to an increase in the amount of lipids; nitrogen limitation was the most effective. Diluted nutrient media (5‐ or 10‐fold) were identified as the best method to stimulate lipid overproduction (60% of DW). The strategy for lipid overproduction consists of the fast growth of P. kessleri culture grown in the complete medium to produce sufficient biomass (DW more than 10 g/L) followed by the dilution of nutrient medium to stop growth and cell division by limitation of all elements, leading to induction of lipid production and accumulation up to 60% DW. Cultivation conditions necessary for maximizing lipid content in P. kessleri biomass generated in a scale‐up solar open thin‐layer photobioreactor were described. Biotechnol. Bioeng. 2013; 110: 97–107. © 2012 Wiley Periodicals, Inc.